2014
DOI: 10.1111/joa.12165
|View full text |Cite
|
Sign up to set email alerts
|

Induction of phosphorylated c‐Jun in neonatal spinal motoneurons after axonal injury is coincident with both motoneuron death and regeneration

Abstract: c-Jun activation has been implicated not only in neuronal degeneration, but also in survival and regeneration. Here, we investigated c-Jun activation in injured motoneurons by using a nerve crush model in neonatal rats. We identified two distinct subpopulations of motoneurons: about 60% underwent degeneration following injury whereas the remaining 40% survived and induced a regeneration response at 3 weeks post injury. However, all motoneurons examined expressed phosphorylated-c-Jun-immunoreactivity (p-c-Jun-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…Adding further complexity to our understanding of NeuN's role in neuronal viability are reports that alterations of NeuN expression show differences in the CNS vs the PNS. Some have reported no altered NeuN expression in axotomized CNS neurons, in contrast to axotomized PNS neurons in which NeuN expression is altered [24,55,59,61]. In our study, a reduced proportion of NeuN+ neurons was observed only in non-axotomized neurons in the acute phase of injury.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Adding further complexity to our understanding of NeuN's role in neuronal viability are reports that alterations of NeuN expression show differences in the CNS vs the PNS. Some have reported no altered NeuN expression in axotomized CNS neurons, in contrast to axotomized PNS neurons in which NeuN expression is altered [24,55,59,61]. In our study, a reduced proportion of NeuN+ neurons was observed only in non-axotomized neurons in the acute phase of injury.…”
Section: Discussioncontrasting
confidence: 81%
“…However, our results demonstrate otherwise, mandating caution when using NeuN to assess neuronal viability or loss following brain injury. This issue has been recently raised in another TBI model [54] as well as in other experimental paradigms in both CNS and PNS [24, 55–61,]. Adding further complexity to our understanding of NeuN’s role in neuronal viability are reports that alterations of NeuN expression show differences in the CNS vs the PNS.…”
Section: Discussionmentioning
confidence: 99%
“…Then we also performed double immunolabeling for p-c-Jun and SMI32 protein (a specific marker of MNs) to quantify the percentage of p-c-Jun expressing SMI32-positive MNs in the ventral horns of the spinal cord. WT animals showed a small percentage (about 8%) of p-c-Jun activated MNs, indicating a physiological activation of stress signaling pathways in healthy tissue, probably due to postnatal axonal refinement (Qu et al, 2013 ; Yuan et al, 2014 ). On the contrary, SMA control mice (PBS-treated) showed a significant increase in p-c-Jun+/SMI32+ expressing cells (39%) compared to WT (Mann-Whitney test; p = 0.0002; Figures 1C,D ).…”
Section: Resultsmentioning
confidence: 99%
“…Male TgCRND8 mice aged 20 months were anesthetized via intraperitoneal injection of ketamine (80 mg/kg) and xylazine (8 mg/kg). The surgical procedures for spinal nerve injury were performed using the described methods in our previous studies [ 39 , 40 , 41 ]. In brief, the right brachial plexus was exposed under an operating microscope at the trunk level through an infraclavicular approach.…”
Section: Methodsmentioning
confidence: 99%